High-surface precision optical device surface adhesive

The inorganic adhesive developed through nano-synthesis technology solves the problems of surface deformation, poor temperature resistance and vacuum exhaust on high-surface precision optical devices, and achieves high-precision, high-temperature resistance and environmentally friendly bonding effects.

CN119592233AInactive Publication Date: 2025-03-11SHANGHAI SHANER NEW MATERIAL TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411884412.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing high-surface precision bonding materials will cause large shrinkage during the curing process, resulting in surface deformation; their temperature resistance is poor and cannot meet the needs of high-temperature processes or usage environments; it is difficult to meet the exhaust requirements under vacuum.

Method used

Using nano-synthetic technology, an inorganic adhesive with nano-scale oxide materials as the main body is synthesized through silicone sources, organic titanium sources, organic tin sources and additives, and environmentally friendly solvents as dispersants. The adhesive is characterized by inorganic composition, nano-scale material particle size and environmentally friendly process.

Benefits of technology

This adhesive does not affect the surface accuracy on the surface of high-surface precision optical devices, has good temperature resistance and high temperature and humidity resistance, and does not exhaust under vacuum, and is suitable for high-precision and high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592233A_ABST
    Figure CN119592233A_ABST
Patent Text Reader

Abstract

The invention discloses a high-surface precision optical device surface adhesive, and relates to the technical field of adhesives. According to the high-surface precision optical device surface adhesive, an inorganic adhesive taking a nanoscale oxide material as a main body is synthesized by adopting a nano synthesis technology, taking an organic silicon source, an organic titanium source, an organic tin source and an auxiliary agent and taking an environment-friendly solvent as a dispersing agent; the adhesive can be used for surface bonding of high-surface precision optical devices, the surface precision is not affected after bonding, the temperature resistance is good, high-temperature and high-humidity resistance is achieved, and exhaust is avoided under vacuum; the cable has the following characteristics: 1, the cable has good temperature resistance and can tolerate the temperature of 300 DEG C for a long time; 2, the particle size of the internal material is about 3-10nm, and the bonding requirement of a high-precision surface type can be completely met by matching with a precise sizing process; and 3, the material is purely inorganic, does not contain organic resin, does not shrink in the curing process, has a thermal expansion coefficient close to that of non-metal oxides such as glass, does not deform during temperature change, and does not influence the surface type of a device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, in particular to a surface adhesive for optical devices with high surface accuracy. Background Art

[0002] High-precision surface refers to the extremely low roughness of the material surface after processing, usually less than 0.1 micron. This processing usually uses mechanical processing first, and then rough polishing, fine polishing, or even electrolytic polishing to obtain extremely low surface roughness. This high-precision surface is generally used in optical systems, such as optical lenses, lenses, reflectors, beam splitters, optical fibers and other devices, which generally need to control the surface accuracy within a relatively high range; in addition, high-precision materials are often used in the process of semiconductor optical devices, such as the use of chemical mechanical polishing technology to polish silicon wafers, gallium arsenide, silicon nitride, gallium nitride and other materials to extremely low roughness to meet the needs of subsequent optical emission or surface reflection.

[0003] The existing high-precision bonding materials are basically organic adhesives composed of resin (thermal curing or UV curing) + solvent or simple organic polymer melt bonding. For example, "UV glue for bonding optical plastics and glass and its preparation method", CN110776870A, its main body is aliphatic isocyanate type polyurethane methacrylate prepolymer, accounting for 25-75% of the weight of the UV glue, and the weight average molecular weight is 10000-35000. "A delayed curing UV glue for bonding optical glass and aluminum sheet", CN114350303A, wherein the main body is a prepolymer accounting for 30-70% of the weight of the UV glue, an epoxy oligomer resin accounting for 20-40% of the weight of the UV glue, and an active monomer accounting for 10-35% of the weight of the UV glue. "A photocurable adhesive for bonding optical glass lenses and its preparation method", CN102167962B, main resin 50%-80%; auxiliary resin 10%-40%; active monomer 5%-20%, the main resin is alicyclic epoxy resin, and the auxiliary resin is modified epoxy acrylate resin. "UV-LED curable optical adhesive, adhesive film and preparation method for bonding electronic glass", CN116694270A, the main components of the optical adhesive are: 50-70 parts of acrylic epoxy copolymer; 10-25 parts of epoxy resin; 10-25 parts of epoxy dilution toughening modifier. "Wafer bonding method", CN118553637A, a spraying device is used to spray molten polyethylene wax on the surface to be bonded of the wafer, and the polyethylene wax is melted and bonded to other surfaces. The above-mentioned adhesive materials are generally suitable for ordinary optical glass bonding or silicon wafer bonding, and can meet the requirements when used in normal environments. However, if they are used for high-precision surface bonding, the following problems will occur: 1. During the curing process, large shrinkage will occur, which will cause surface deformation. In this way, the meaning of the high-precision surface obtained through complex high-precision processing technology will be completely lost, causing the entire device to lose its value; 2. Poor temperature resistance. Generally, the temperature resistance of organic resins is less than 150°C, and even worse, less than 100 degrees Celsius. Therefore, for systems with subsequent high-temperature processes or high-temperature use environments, this type of adhesive material is meaningless and will have catastrophic consequences in subsequent use; 3. It is difficult to meet the exhaust requirements under vacuum. Many optical devices have vacuum requirements in their use environment or subsequent processes. Organic materials use 10-30% of organic small molecules as cross-linking agents, auxiliary agents or solvents during the preparation process. These small organic molecules are not completely released under normal pressure, but are gradually released when encountering a vacuum, causing the exhaust rate in the device's use environment to exceed the standard. In addition, along with the precipitation of small molecules, the adhesive itself is also disintegrating and gradually losing its adhesion.

[0004] In order to solve the above problems of organic adhesives, the industry has developed semi-organic and semi-inorganic adhesives. "An Adhesive for Ceramic Materials and Preparation Method", CN115011297B, includes component A and component B, the weight ratio of the two components A and B is A:B=2:1, wherein component A is composed of the following components in parts by weight: 90-150 parts of mixed epoxy resin, 10-30 parts of homemade toughening agent, 10-15 parts of diluent, 80-120 parts of alumina powder, 20-40 parts of heavy calcium carbonate, 20-40 parts of fibrous filler, 15-30 parts of fumed silica, and 3-5 parts of silane coupling agent; component B is composed of the following components in parts by weight: composite curing agent for ceramic adhesive Agent 40-60 parts, curing accelerator 1-5 parts, alumina powder 50-80 parts, heavy calcium carbonate 30-50 parts, fibrous filler 5-10 parts, fumed silica 3-8 parts, silane coupling agent 1-3 parts; "A glass adhesive and its preparation method", CN107418484A, its main formula is: ethylene carbonate 2-8 parts, zinc oxide 1-3 parts, ethylene carbonate 3-6 parts, curing agent 1-3 parts, coupling agent 0.5-1 parts, liquid nitrile rubber 3-6 parts, accelerator 1-2 parts, phenolic resin 3-7 parts, silicon dioxide 2-4 parts and emulsified silicone oil 1-3 parts.

[0005] The above-mentioned adhesives generally use organic resins as the main bonding material and inorganic oxides such as silicon oxide, aluminum oxide, calcium carbonate, zinc oxide and other oxides as fillers to reduce the thermal expansion coefficient of organic matter or improve the temperature resistance of the adhesive. This type of adhesive is generally used for bonding relatively rough surfaces. Because this type of adhesive uses a large amount of metal or non-metal oxides, its particle size is generally in the micron level or even hundreds of microns, which is not suitable for bonding surfaces with a surface accuracy of less than 0.1 microns.

[0006] In order to obtain an extremely low thermal expansion coefficient, the industry has also developed a fully inorganic adhesive, "An inorganic adhesive and its preparation method", CN117777903A, including the following raw materials in weight: 20-35 parts of acrylic masterbatch, 8-16 parts of silica sol, 5-12 parts of embedded silica ferromagnetic beads, 10-20 parts of phosphate solution, 5-15 parts of sodium aluminum silicate, and 30-50 parts of deionized water; "A method for preparing industrial sodium silicate adhesive", CN107090250A, mix high-quality industrial sodium silicate with 2 times the resin emulsion, add it to silica sand, and mix thoroughly to obtain water glass adhesive.

[0007] The biggest feature of this type of adhesive is that it is made entirely of inorganic materials, has a certain temperature resistance, can reach temperatures above 300°C, and does not release gas under vacuum. It is mainly used for high-temperature kiln surface protection or surface bonding with heat resistance requirements. However, this type of material generally uses inorganic oxide particles above the micron level as the main material, so it is impossible to achieve bonding of high-precision surfaces below 0.1 microns. Summary of the invention

[0008] In view of the deficiencies of the prior art, the present invention provides a surface adhesive for optical devices with high surface accuracy, which solves the problems mentioned in the above background technology.

[0009] To achieve the above objectives, the present invention is implemented through the following technical scheme: a high-precision optical device surface adhesive, including the following components: one or more of an organic silicon source, an organic titanium source, an organic tin source, an acid, deionized water, a low-grade alcohol, nitrogen, and an additive.

[0010] Preferably, the organosilicon source is selected from any one of silane coupling agent, methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, butyl orthosilicate, organosilicon prepolymer and organosilicon oil.

[0011] Preferably, the organic titanium source is selected from any one of tetraethyl titanate, tetrapropyl titanate, tetrabutyl titanate and a titanate coupling agent.

[0012] Preferably, the organic tin source is selected from any one of tetrabutyl stannate and tin chloride pentahydrate.

[0013] Preferably, the acid is selected from any one of an organic acid and an inorganic acid.

[0014] Preferably, the organic acid includes malic acid, citric acid, tartaric acid, oxalic acid, and aminosulfonic acid.

[0015] Preferably, the inorganic acid includes hydrochloric acid, nitric acid, sulfuric acid, boric acid, and phosphoric acid.

[0016] Preferably, the lower alcohol is selected from one or more of methanol, ethanol, isopropanol, butanol, pentanol, propylene glycol and glycerol.

[0017] Preferably, the auxiliary agent is a silane coupling agent.

[0018] Preferably, the preparation method of the high surface precision optical device surface adhesive is:

[0019] Step 1: dissolving an organic titanium source in a lower alcohol to prepare a 1-20% solution, and marking it as A;

[0020] Step 2: dissolving the acid in deionized water to prepare a 0.1-10% solution, and marking it as B;

[0021] Step 3, placing solution A in a high pressure reactor and heating it to 80°C;

[0022] Step 4: gradually add B into A to obtain C, the addition time is 0.5-3h;

[0023] Step 5: dissolve the organosilicon source in a lower alcohol to prepare a 0.5-5% solution, and add it to C at one time;

[0024] Step 6: Then fill with nitrogen, the pressure range is 0.1-1MPa;

[0025] Step 7, maintaining the temperature and pressure for reaction for 0.5-24h;

[0026] Step 8: gradually cool to room temperature and age for 48 hours to obtain a nano-scale inorganic adhesive.

[0027] Beneficial Effects

[0028] The present invention provides a high-precision optical device surface adhesive. Compared with the prior art, the high-precision optical device surface adhesive has the following beneficial effects: the high-precision optical device surface adhesive adopts nano-synthesis technology, uses organic silicon source, organic titanium source, organic tin source and auxiliary agent, and uses environmentally friendly solvent as dispersant to synthesize an inorganic adhesive with nano-grade oxide material as the main body; it can be used for surface bonding of high-precision optical devices, and does not affect the surface accuracy after bonding, has good temperature resistance, high temperature and high humidity resistance, and does not exhaust under vacuum; its characteristics are as follows: 1. Good temperature resistance, can withstand 300°C temperature for a long time; 2. The particle size of its internal material is about 3-10nm, and with the precision sizing process, it can fully meet the bonding requirements of high-precision surfaces; 3. It is purely inorganic and does not contain organic resin. It does not shrink during the curing process. The thermal expansion coefficient of the material itself is close to that of non-metallic oxides such as glass. It will not deform when the temperature changes, and will not affect the device surface; 4. It does not exhaust under vacuum, and does not affect the vacuum of the system; 5. It is resistant to high temperature and high humidity. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A test chart of the heat resistance performance of an adhesive provided for a surface adhesive of an optical device with high surface precision according to the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] Tetrabutyl titanate is dissolved in ethanol to prepare a 1% solution, which is marked as A; hydrochloric acid is dissolved in deionized water to prepare a 0.1% solution, which is marked as B; solution A is placed in a high-pressure reactor and heated to 80°C; B is gradually added dropwise into A to obtain C, with the addition time being 0.5h; methyltriethoxysilane is dissolved in ethanol to prepare a 0.5% solution, which is added to C at one time; nitrogen is then filled in, with a pressure range of 0.1MPa; the temperature and pressure are maintained for reaction for 0.5h; the adhesive material can be obtained by gradually cooling to room temperature and aging for 48h.

[0033] Example 2

[0034] Dissolve tetrabutyl titanate in ethanol to prepare a 20% solution, and mark it as A; dissolve hydrochloric acid in deionized water to prepare a 10% solution, and mark it as B; put the A solution into a high-pressure reactor and heat it to 80°C; gradually add B into A to obtain C, and the dropping time is 3 hours; dissolve methyltriethoxysilane in ethanol to prepare a 5% solution, and add it to C at one time; then fill with nitrogen, and the pressure range is 1MPa; maintain the temperature and pressure for 24 hours; gradually cool to room temperature, and age for 48 hours to obtain the bonding material

[0035] Example 3

[0036] Tetraethyl titanate is dissolved in isopropanol to prepare a 10% solution, which is marked as A; citric acid is dissolved in deionized water to prepare a 5% solution, which is marked as B; solution A is placed in a high-pressure reactor and heated to 80°C; B is gradually added dropwise into A to obtain C, with the addition time being 2 hours; methyl orthosilicate is dissolved in isopropanol to prepare a 3% solution, which is added to C at one time; nitrogen is then filled in with a pressure range of 0.5 MPa; the temperature and pressure are maintained for reaction for 10 hours; the solution is gradually cooled to room temperature and aged for 48 hours to obtain a nanoscale inorganic adhesive.

[0037] Example 4

[0038] Tetraethyl titanate is dissolved in methanol to prepare a 15% solution, which is marked as A; boric acid is dissolved in deionized water to prepare an 8% solution, which is marked as B; solution A is placed in a high-pressure reactor and heated to 80°C; B is gradually added dropwise into A to obtain C, with the addition time being 1.5 hours; ethyl orthosilicate is dissolved in methanol to prepare a 4% solution, which is added to C at one time; nitrogen is then filled in, with a pressure range of 0.8 MPa; the temperature and pressure are maintained for reaction for 15 hours; the solution is gradually cooled to room temperature and aged for 48 hours to obtain a nanoscale inorganic adhesive.

[0039] Example 5

[0040] Tetrabutyl titanate is dissolved in propylene glycol to prepare an 18% solution, which is marked as A; boric acid is dissolved in deionized water to prepare a 9% solution, which is marked as B; solution A is placed in a high-pressure reactor and heated to 80°C; B is gradually added dropwise into A to obtain C, with the addition time being 2.5 hours; butyl orthosilicate is dissolved in propylene glycol to prepare a 4.5% solution, which is added to C at one time; nitrogen is then filled in, with a pressure range of 0.6 MPa; the temperature and pressure are maintained for reaction for 22 hours; the solution is gradually cooled to room temperature and aged for 48 hours to obtain a nanoscale inorganic adhesive.

[0041] UV resistance test: The sample was coated on a glass slide (the coating thickness was 30 um), and irradiated with ultraviolet light at an intensity of 15 mw / cm for 3 minutes. The yellowing index of the coating film aged for 30 days at 1 mw / cm UV radiation was tested according to ASTM D2095 standard; the results are shown in Table 1.

[0042] Shear strength test: The shear strength of the present application was tested at 23°C, 60°C and 100°C according to GB / T7124-2008 standard; the results are shown in Table 1.

[0043] Yellowing Index / YI Shear Strength Example 1 33.18 30.64 Example 2 34.92 30.58 Example 3 33.07 30.96 Example 4 35.08 30.83 Example 5 34.54 30.27

[0044] At the same time, the contents not described in detail in this specification belong to the existing

[0045] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0046] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high-precision optical device surface adhesive, characterized in that: The invention comprises the following components: one or more of an organic silicon source, an organic titanium source, an organic tin source, an acid, deionized water, a low-grade alcohol, nitrogen and an auxiliary agent.

2. The high-precision optical device surface adhesive according to claim 1, characterized in that: The organic silicon source is selected from any one of silane coupling agent, methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, butyl orthosilicate, organic silicon prepolymer and organic silicon oil.

3. The high-precision optical device surface adhesive according to claim 1, characterized in that: The organic titanium source is selected from any one of tetraethyl titanate, tetrapropyl titanate, tetrabutyl titanate and a titanate coupling agent.

4. The high-precision optical device surface adhesive according to claim 1, characterized in that: The organic tin source is selected from any one of tetrabutyl stannate and tin chloride pentahydrate.

5. The high-precision optical device surface adhesive according to claim 1, characterized in that: The acid is selected from any one of an organic acid and an inorganic acid.

6. The high-precision optical device surface adhesive according to claim 5, characterized in that: The organic acid includes malic acid, citric acid, tartaric acid, oxalic acid, and aminosulfonic acid.

7. The high-precision optical device surface adhesive according to claim 5, characterized in that: The inorganic acid includes hydrochloric acid, nitric acid, sulfuric acid, boric acid and phosphoric acid.

8. The high-precision optical device surface adhesive according to claim 1, characterized in that: The lower alcohol is selected from one or more of methanol, ethanol, isopropanol, butanol, pentanol, propylene glycol, and glycerol.

9. The high-precision optical device surface adhesive according to claim 1, characterized in that: The auxiliary agent is a silane coupling agent.

10. The high-precision optical device surface adhesive according to claim 1, characterized in that: The preparation method of the high-precision optical device surface adhesive is as follows: Step 1: dissolving an organic titanium source in a lower alcohol to prepare a 1-20% solution, and marking it as A; Step 2: dissolving the acid in deionized water to prepare a 0.1-10% solution, and marking it as B; Step 3, placing solution A in a high pressure reactor and heating it to 80°C; Step 4: gradually add B into A to obtain C, the addition time is 0.5-3h; Step 5: dissolve the organosilicon source in a lower alcohol to prepare a 0.5-5% solution, and add it to C at one time; Step 6: Then fill with nitrogen, the pressure range is 0.1-1MPa; Step 7, maintaining the temperature and pressure for reaction for 0.5-24h; Step 8: gradually cool to room temperature and age for 48 hours to obtain a nano-scale inorganic adhesive.

Citation Information

Patent Citations

  • Photocuring adhesive used for adhering optic glass lenses and preparation method thereof

    CN102167962B

  • Method for preparing industrial sodium silicate adhesive

    CN107090250A

  • Glass adhesive and preparation method thereof

    CN107418484A